Раціональне кредитне забезпечення інвестиційних проектів підприємств України - Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Trusova, Natalia; Вигоднер, І. В. (My University, 2018)
UK: Обґрунтовано вихідні положення кредитних відносин, на які спирається теорія та практика раціонального кредитного процесу, а також техніка й технологія надання та повернення кредиту. Запропоновано модель раціонування кредиту для аграрних підприємств з урахуванням зміни структури банківського фінансування. Застосовано диференційований підхід раціонального кредитування до окремого позичальника, який за ефективної реалізації програми фінансування інвестиційних проектів в сільському господарстві забезпечує дохідність банківських кредитних операцій. EN: The theoretical and methodological foundations for rational security of investment projects of agricultural enterprises in Ukraine are considered. It is proved the agricultural micro environment depends on changes in terms of financing agriculture. This affects the access of economic entities to the efficient reallocation of credit resources to ensure the effectiveness of investment projects. Formally, the real value of the loan as a financial tool of investment activity of agricultural enterprises have not formed an appropriate regulatory policy on the mechanism of credit support of sustainable agriculture and strengthening national security, which in turn inhibits the growth of qualitative and quantitative indicators of investment activity and the financial capacity of businesses. Assumptions of credit relations, which are based on the theory and practice of credit management process, as well as equipment and technology provision and repayment, are grounded. The composition of credit security of investment projects of agricultural enterprises on the basis of credit and regulatory policy regarding the functioning of the market for loans is defined. It is proved that the system of credit and investment cooperation in the interaction of companies provides guarantee to banks reinsurance risk of default at the loss of a stable financial potential of agricultural sectors and enterprises. The model of credit rationing for agricultural enterprises considering the changes in the structure of bank financing is suggested. The differentiated approach of rational lending to a single borrower is applied. This approach ensures the profitability of bank lending operations on the effective implementation of the program of financing investment projects in agriculture.
Rational credit security of investment projects of enterprises in Ukraine
Keywords: кредит; кредитні ресурси; кредитний ризик; фінансування; кредитування; інвестиційні проекти; аграрні підприємства; credit; loans; credit risk; financing; lending; investment projects; agricultural enterprises